Stability and Deformation Analysis of Landslide under Coupling Effect of Rainfall and Reservoir Drawdown - Muhammad Shoaib; Wang Yang; Yang Liang; Gohar Rehman (Salehan Institute of Higher Education, 2021)
Landslides, a devastating hazard, continue to happen, affecting the lives of thousands of people each year. Fluctuation in the Reservoir Water Level (FRWL) is one of the leading features disturbing the slope stability in reservoir areas, drawdown is more crucial than the rise to the stability of landslide. Latest studies grounded on field investigation and monitoring data propose that landslides in reservoir areas are initiated not solely by one issue like precipitation or FRWL, however conjointly by their joint actions. Zhulinwan landslide in Chongqing, China, Three Gorges Reservoir (TGR) area was analyzed by field investigation and numerical modelling to evaluate the characteristics of the landslide. The changes in landslide stability and deformation under the effect of reservoir drawdown and rainfall is analyzed using GEOSLOPE Software. The seepage analysis is done using SEEP W Model, afterward deformation and stability analysis using SLOPE W and SIGMA W respectively. The analysis confirmed that the coupling effect of reservoir drawdown at 1.2 m/d and rainstorm of once in 50 years return period makes the landslide unstable. Moreover, deformation at the same condition is maximum 0.049 m. The findings may be used by local authorities to help make decisions about slope stabilization in the event of a confirmed significant rainfall event. Doi: 10.28991/cej-2021-03091713 Full Text: PDF